Mapping the geological fault zone that triggered the Mw 6.1 Pasaman earthquake in Indonesia on the basis of gravity anomalies - Yanis, Muhammad; Ananda, Riski; Adhari, Muhammad Ridha; Paembonan, Andri Yadi; Ghani, Azman Abdul (Geologos, 2025)
Indonesia’s Great Sumatran Fault (GSF) is well known for its destructive capability, having generated many moderate to strong earthquakes, causing damage. A better understanding of GSF characteristics is needed to mitigate future geological hazards in Sumatra and prevent unnecessary loss and damages. The present research aims to map the fault structure in West Pasaman, Indonesia, using the Topex satellite and global gravity model plus (GGM+). Residual anomalies from Bouguer data (50–80 mGal) show a continuous pattern between the confluence of the Angkola, Sumpur and Sianok fault segments in the Pasaman. The vertical and horizontal derivatives were also applied in order to clarify fault structure, which is demonstrated by high derivative anomalies (0.05–0.08 mGal/m) in the horizontal and 0.1 mGal/m in the vertical. Moreover, a cross sectional model from the 3D algorithm (Occam and Singular Value Decomposition) may show the presence of several segments/faults in the Pasaman region, such as the Angkola, Barumun and Sumpur faults with high-density values of ρ = 2.3–2.4 g/cm3. Based on results obtained, the use of Topex and GGM+ has provided an overview of the effectiveness of global gravity in mapping faults in the Pasaman region. It is a time-consuming, yet inexpensive method that can be applied to other areas, especially those that are difficult to reach.